Financial Coping Strategies of selected families in Enugu State in the face of Economic Recession in Nigeria - I.P., Ogbonne (Journal of Home Economics Research, 2024)
The major purpose of this study was to determine the financial coping strategies families have adopted to survive in the current economic recession in Nigeria. The area of the study was Enugu State. The sample was 384 while the population was 16,491,395. The instrument of data collection was the questionnaire. Data analysis was done using mean and standard deviation. Major findings of the study revealed that the financial coping strategies families have adopted to survive economic recession include: family budging, saving plan, debt reduction plan, modification in basic needs like food, shelter, education as well as investment strategies like saving target, spending plan among others. Based on the result of this stud, it is recommended, among others, that heads of households should always take the wellness of the family into account while implementing coping strategies.